Integrating local culture into web-based mobile-assisted language learning: A mixed-methods study on secondary school EFL students’ reading comprehension - Vina Agustiana (Universitas Islam Negeri Ar-Raniry, 2026)
The insufficient integration of local cultural content into technology-enhanced English instruction may diminish the relevance and pedagogical effectiveness of reading activities in secondary English as a Foreign Language (EFL) classroom. This study investigated the extent to which incorporating local culture into a web-based Mobile-Assisted Language Learning (MALL) environment improves ninth-grade students' reading comprehension and examined their perceptions of its implementation. Employing a one-group pretest–posttest quasi-experimental design within a mixed-methods framework, the study involved 379 students and two English teachers at an Indonesian secondary school. Quantitative data were collected through pre- and post-tests, while qualitative and perceptual data were obtained from semi-structured interviews and a student attitude questionnaire. The results revealed a statistically significant improvement in reading comprehension, with an average N-Gain score of 0.33, indicating a moderate learning effect. Furthermore, students reported positive perceptions of the platform's cultural relevance and engagement. These findings suggest that culturally responsive MALL-based instruction can enhance both learning outcomes and learner motivation, offering practical implications for integrating local cultural content into technology-enhanced English language teaching at the secondary level.